Pornography and Rape Problem: สื่อลามกอานาจารกับปัญหาการข่มขืน - Jirasatthumb, Norachit; Jearviriyaboonya, Jakkrich; Reechaiwijitkun, Pongsathorn (Journal of Applied Economics and Management Strategy, 2020)
บทคัดย่อ บทความวิจัยนี้มีวัตถุประสงค์เพื่อต้องการศึกษาความสัมพันธ์ระหว่างตัวแปรต้น คือ ระดับการปิดกั้นสื่อ กฎหมายควบคุมสื่อลามกอนาจาร และ ความรุนแรงของบทลงโทษผู้ก่อคดีข่มขืน กับ ตัวแปรตาม ได้แก่ อัตราการข่มขืน บทความวิจัยนี้ใช้แบบจำลอง Random Effect Model (REM) ทางเศรษฐมิติในการประมาณค่าพารามิเตอร์จากข้อมูลภาคตัดขวางผสมกับอนุกรมเวลา ผลการศึกษาพบว่า การเพิ่มขึ้นของระดับการปิดกั้นสื่อมีผลทำให้อัตราการข่มขืนลดลง ส่วนการที่ให้สื่อลามกฯ ถูกกฎหมายนั้นส่งผลให้อัตราการข่มขืนลดลง และ ความรุนแรงของบทลงโทษหรือการมีโทษประหาร สัมพันธ์กับอัตราการข่มขืนในทิศทางตรงกันข้าม ผู้วิจัย จึงเสนอว่า (1) สื่อลามกอนาจารควรทำให้ถูกกฎหมาย ควบคู่กับการกำกับให้ผู้ชมเข้าถึงสื่อลามกฯ ได้อย่างเหมาะกับช่วงอายุและอย่างมีวิจารณญาณ และ (2) การออกแบบนโยบายที่เกี่ยวกับการปราบปรามผู้กระทำผิด ในคดีข่มขืน ต้องคำนึงถึงประเด็นเรื่องความรุนแรงของบทลงโทษ ควบคู่กับความพยายามในการเพิ่มโอกาสในการจับกุมผู้กระทำผิด Abstract This research article aims to study the relationship between dependent variables which are pornography control law, level of press censorship, and level of legal penalty to rape offender, and independent variable which is rape rate. This research article employs the econometric model of random effect (RM) to estimate parameters from panel data. The results show that the increase in the level of press censorship leads to a decrease in rape rate. Legalizing pornography leads to the reduction in rape rate. And the level of legal penalty to or capital punishment to rape offender negatively related to rape rate. Researchers suggest that (1) pornography should be legalized together with the press control to make sure that audiences are able to access media content that is suitable for age range and with discretion, and (2) policy designed to suppress rape offenders need to consider the issue of penalty level alongside the attempt to increase the chance to arrest rape offenders.